2017
DOI: 10.1091/mbc.e16-08-0594
|View full text |Cite
|
Sign up to set email alerts
|

TRIM9-dependent ubiquitination of DCC constrains kinase signaling, exocytosis, and axon branching

Abstract: In the presence of netrin, tripartite motif protein 9 (TRIM9) promotes deleted in colorectal cancer (DCC) clustering, but TRIM9-dependent ubiquitination of DCC is reduced. Loss of ubiquitination promotes an interaction between DCC and FAK and FAK activation. FAK activation is required for the progression from SNARE assembly to exocytic vesicle fusion, which supplies membrane material for axon branching.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 58 publications
3
58
3
Order By: Relevance
“…This indicated the ligase domain was unnecessary to constrain exocytosis, but required for response to netrin. Although previous studies identified TRIM9-dependent ubiquitination of substrates as a mechanism to alter substrate function (Menon et al, 2015;Plooster et al, 2017), we did not observe netrin-1 or TRIM9-dependent changes in the ubiquitination of SNAP25 ( Figure S4C), suggesting that ubiquitin-dependent modulation of SNAP25 did not explain TRIM9-dependent changes in exocytosis. Expression of TRIM9ΔSPRY or TRIM9ΔCC failed to reduce the elevated frequency of exocytosis in the neurites (P = 0.23 and P = 0.33, respectively, Figure 5C) or the netrin-dependent reduction in temporal clustering ( Figure S4B).…”
Section: Different Domains Of Trim9 Modulate Specific Parameters Of Econtrasting
confidence: 93%
See 1 more Smart Citation
“…This indicated the ligase domain was unnecessary to constrain exocytosis, but required for response to netrin. Although previous studies identified TRIM9-dependent ubiquitination of substrates as a mechanism to alter substrate function (Menon et al, 2015;Plooster et al, 2017), we did not observe netrin-1 or TRIM9-dependent changes in the ubiquitination of SNAP25 ( Figure S4C), suggesting that ubiquitin-dependent modulation of SNAP25 did not explain TRIM9-dependent changes in exocytosis. Expression of TRIM9ΔSPRY or TRIM9ΔCC failed to reduce the elevated frequency of exocytosis in the neurites (P = 0.23 and P = 0.33, respectively, Figure 5C) or the netrin-dependent reduction in temporal clustering ( Figure S4B).…”
Section: Different Domains Of Trim9 Modulate Specific Parameters Of Econtrasting
confidence: 93%
“…A potential range of vesicular surface areas was approximated from vesicle diameters measured from transmission electron microscopy (TEM) images of cortical neurons at 48 hours in vitro, with the assumption that vesicles were spherical ( Figure 3A). To correct for capturing random slices through vesicles, we took the conservative estimate that the 25th percent of the interquartile range represented the diameter of the smallest vesicles (80 nm) and the 75th percent of the interquartile-range represented the diameter of largest vesicles (130 nm, Plooster and Menon et al, 2017). We estimated membrane addition between 24 and 48 hours in vitro, using the formula where y represents the predicted neuronal surface area at 48 hours, S is the neuronal surface area at 24 hours, f24 and f48 are the exocytic frequency at 24 and 48 hours, respectively, and z is the surface area of vesicles.…”
Section: A Mathematical Approximation Of Membrane Expansion In Develomentioning
confidence: 99%
“…TRIM9 also interacts with and ubiquitinates DCC, a transmembrane receptor for netrin-1 [5,17], and the actin polymerase VASP [8]. Upon binding of netrin-1 to its receptor DCC, TRIM9 releases SNAP25 and VASP is deubiquitinated, promoting vesicle fusion, membrane expansion, and membrane protrusion [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ena/vasodilator stimulated phosphoprotein (VASP) actin polymerases are critical to filopodia formation and maintenance in neurons (Dent et al, 2007; Kwiatkowski et al, 2007), particularly downstream of DCC and netrin-1 (Lebrand et al, 2004). Recent work demonstrated that negative regulation of downstream effectors primes the neuron for appropriate netrin response (Menon et al, 2015; Plooster et al, 2017). For example, E3 ubiquitin ligase tripartite motif protein 9 (TRIM9) is required for ubiquitination and inhibition of the actin polymerase VASP (Menon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%